Evaluation of Surgical Clipping and Endovascular Coiling on Oculomotor Nerve Palsy Caused by Internal Carotid Artery Aneurysm - Sun, Zhenqing; Yan, Xueqiang; Li, Xiaolong; Wu, Jie (Frontiers in Neurology, 2020)
Objectives: Internal carotid artery (ICA) aneurysm often leads to oculomotor nerve palsy (ONP) that impairs eye movement. Currently, microsurgical clipping and endovascular coiling are the two major options to treat ONP. The purpose of the current study is to compare the clinical outcomes of the two methods in patients with ONP caused by ICA aneurysm. Patients and Methods: In the present study, we assessed the prognostic factors and recovery outcomes of a total of 90 ICA aneurysm-induced ONP patients, where 50 of them were treated with microsurgical clipping and 40 of them were treated with endovascular coiling. Within the endovascular coiling group, 20 of the patients were treated with balloon-assisted coiling and the other 20 were treated with stent-assisted coiling. Results: Overall, we achieved a 59% (53 out of 90) full recovery rate. Both surgical clipping and endovascular coiling treatment methods achieved similar recovery outcomes in the tested patients. However, within the endovascular coiling group balloon-assisted coiling treatment demonstrated a significantly higher full recovery rate (17 out of 20) compared to stent-assisted coiling treatment (8 out of 20). Conclusion: In general, no significant difference was identified between the surgical and coiling treatments and both procedures were considered as beneficial for ICA aneurysm-induced ONP.